Arte contemporânea, mídia-educação e museus: remixando uma proposta pedagógica para o ensino médio - SOARES, Lizandra Calife (2017)
This research aimed at the creation of a digital educational resource targeted to the Secondary School, by building interactions between the teaching of contemporary art, media-education and museums on the web. It answers the fundamental question: how to integrate the collections of contemporary art - arranged in international and national virtual museums - with the national curricular demands of the Secondary School, in a coherent and contextualized proposal that integrates the methodologies of the media education and art education? The specific goals were to investigate the contribution of media education pedagogical approaches to the arts education field; to test possibilities of interconnection between arts teaching and media education, from activities that relate the creativity and production processes of the artist with the public appreciation, in a context of coding/decoding and experimentation with the aesthetic information of contemporary arts. The theoretical background is based on Dewey (1934, 1979); Eisner (1978, 2008) and Bruner (2000), and their conceptions and recommendations for the field of Education em general and the teaching of the arts in particular. Also, we recovered the foundations of the Reader's Response Theory (FISH, 1980) related to the so-called social literacy (STREET, 2014), brings up the media literacy applied to arts. For this research were also analyzed studies referring to the methodologies of teaching art developed in Brazil (BARBOSA, 1995, 2003, 2010, 2011, 2015) and media, also observed in the national educational documents (PCN’s-EM /2000; PCN’s+EM /2002; OC’s-EM /2006). As a methodological procedure, it is an applied and qualitative research with exploratory character, bibliographical and iconological proceedings. The production was based on the methodological conceptions of the design of products, to create and assess a production process that will generate the final product. At the conclusion of the research, a digital educational resource was built based on free technologies, which will support the study of contemporary arts in Secondary School, focusing on criticism of a knowledge builder and the media as an informal educator in society.